Feasibility study of a sensor-based autonomous load control exercise training system for COPD patients - Song, Bianying; Becker, Marcus; Gietzelt, Matthias; Haux, Reinhold; Kohlmann, Martin; Schulze, Mareike; Tegtbur, Uwe; Wolf, Klaus-Hendrik; Marschollek, Michael (Journal of medical systems, 2015)
Decision support systems (DSSs) which are able to automatically supervise and control physical exercise training of patients affected by chronic obstructive pulmonary disease (COPD) are regarded as a novel method to promote rehabilitation. The objective of our research work for this paper was to evaluate the feasibility of a rule-based DSS for autonomous bicycle ergometer training of COPD patients. Load control is based on real-time analysis of sensor parameters oxygen saturation and heart rate. Ten COPD patients have participated in a study, performing altogether 18 training sessions. On average, 7.4 rules were fired in each training session. Four sessions had to be stopped for different reasons. The average ergometer training load ranged between 31 and 47 W. The average percentage of heart rate in or lower than the intended target zone was 45.9 and 41.6 %, respectively. The average patient-perceived Borg value was 12.6 ± 2.4. Patients reported a high satisfaction for the automatically controlled training. With the help of the DSS, patients may change their training place from a rehabilitation center to their own homes. More studies are needed to assess long-term clinical and motivational effects of the DSS in home environment.
Published online: 16 November 2014
Gesehen am 19.06.2020